Exploring the Quality of Services and Facilities in Increasing Guest Satisfaction at Villa Cantik Tresna Seminyak - Setiawan, Agung; Sari, Meci Nilam (GAYAKU PUBLISHER, 2024)
This study aims to explore the variables of service quality and facilities on guest satisfaction staying at Villa Cantik Tresna Seminyak. The method used is to conduct literature studies from 10 books and journals and then conduct cognitive analysis related to the relationship between service quality and facilities and customer satisfaction. Opinions and points of view found in 10 books and journals are then taken as important points related to the problem being studied. The results of the literature study of 10 books and journals that have been reviewed by researchers show that there are several kinds of views or statements related to improving service quality and service. Suggestions that researchers can give to the management of Villa Cantik Tresna are: (1) Provide maximum service to guests who stay. (2) Repairing villa facilities that are damaged or outdated because they can interfere with the view and affect guest assessments of villa facilities. (3) Pro-actively asking guests or customers about impressions and messages during their stay so that management knows where guests or customers are dissatisfied.